O serviço de referência em bibliotecas e a proxemia: as práticas de relação, percepção e intervenção do bibliotecário na mediação da informação com o usuário - QUEIROZ, Éder Ney do Rosário (2017)
Analysis of the reference service in relation to the personal service provided by the librarian to the user and the proxemia, with the purpose of clarifying how the reference sector can contribute and be configured as mediation tool before the librarian's perception in the spatial behavior with the user . For this, we sought to reflect on this interpersonal relationship established regarding the pleasant and unpleasant states that occur in the space of the library, for its transformation in the act of mediation of information. As a methodological procedure, the research is characterized as exploratory, seeking a better understanding of the investigated phenomenon, being adopted the bibliographic research in records resulting from previous researches made and published by other authors, available in books, articles and other documents. Thus, in what concerns the service of reference, were adopted, among others, Ranganathan (2009), Grogan (1995/2001), Macedo (1990), Mendonça (2005) and Almeida Júnior (2009). Regarding the spatial behavior (proxemia) of the user's library authors such as Edward T. Hall (1977), Umberto Eco and Michel Maffesoli were studied. As a result, we observed with the concepts used to address topics that encompass personal service in the referral service and the theory called proxemia that makes observations to the space needs of the man, as this relates both personal and social, during their communication. The service of reference in its strict sense, that is, personal service, configures an existing relationship between the user and the librarian, thus, there is also a distance between these individuals according to the proxemic theory, which can establish a relation of Confidence in the user, where the visual contact and approach can translate it that the librarian is attentive and available to the questions posed by him, favoring more spontaneous exchanges, generating a better interaction and providing pleasant states and resulting in a more efficient and effective mediation of information. effective. Concluding the research, it is considered that the relation of the service of reference with the personal service performed by the librarian to the user with the study of pleasant and unpleasant states during his spatial occupation treated by the proxemic theory becomes an analysis of considerable importance for an effective mediation Information in the library space.